Colloidal lithography for fabricating patterned polymer-brush microstructures - Chen, Tao; Chang, Debby P.; Jordan, Rainer; Zauscher, Stefan (Beilstein Journal of Nanotechnology, 2012)
We exploit a series of robust, but simple and convenient colloidal lithography (CL) approaches, using a microsphere array as a mask or as a guiding template, and combine this with surface-initiated atom-transfer radical polymerization (SI-ATRP) to fabricate patterned polymer-brush microstructures. The advantages of the CL technique over other lithographic approaches for the fabrication of patterned polymer brushes are (i) that it can be carried out with commercially available colloidal particles at a relatively low cost, (ii) that no complex equipment is required to create the patterned templates with micro- and nanoscale features, and (iii) that polymer brush features are controlled simply by changing the size or chemical functionality of the microspheres or the substrate.
Keywords: atom-transfer radical polymerization; colloidal lithography; patterning; self-assembled microsphere monolayer